The Integration Value of Phra Buddha Chinnarat That Influences Lives of Thai People - Chanhom, Phar Boonlayadej Techapunyo; Khammuangsaen, Boonruam; Ponsen, Kitsuchin (Journal of Dhamma for Life, 2024)
This research aims to 1) study the values of Phra Buddha Chinnarat, 2) examine the lifestyle of Thai people, 3) integrate the values of Phra Buddha Chinnarat that influence the lifestyle of Thai people, and 4) present knowledge on the integration of Phra Buddha Chinnarat’s values that influence the lifestyle of Thai people. This qualitative research primarily involves studying and analyzing information from the Tripitaka, related texts, and documents, as well as conducting in-depth interviews. The key informants consist of three groups: 1) five Sangha administrators, 2) five scholars, and 3) five government officials, all of whom reside in Phitsanulok Province, totaling 15 individuals. The data were analyzed descriptively. The research findings are as follows: 1) The values of Phra Buddha Chinnarat are seen as a conceptual medium encouraging intellectual reasoning. Worshippers of Phra Buddha Chinnarat perceive its value and significance in three aspects: historical, Buddhist art, and aesthetics, all of which have a psychological impact. 2) The lifestyle of Thai people, including Sangha administrators, scholars, and government officials, shows that the values and significance of Phra Buddha Chinnarat affect their lives in terms of economy, safety, fortune, and psychological faith. 3) The integration of Phra Buddha Chinnarat’s values influencing the lifestyle of Thai people reveals that Phra Buddha Chinnarat, as a medium of historical, artistic, and aesthetic value, benefits individuals psychologically, socially, culturally, and economically. 4) The knowledge model regarding the integration of Phra Buddha Chinnarat’s values that influence the lifestyle of Thai people is identified as the “ADM Model.” This model consists of: A (Abstain from doing bad things): refraining from all evil deeds, D (Do good deeds): following Buddhist teachings according to one’s role and status. M (Make your mind bright): achieving mental clarity, cleanliness, and tranquility. In conclusion, the ADM Model is a principle derived from integrating the values of Phra Buddha Chinnarat to align with the lifestyle of Thai people.